Sosialisasi Kesadaran Keamanan Penggunaan Smartphone Bagi Siswa/i SMP Islam Imam Syafii, Desa Kabasiran Kecamatan Parung Panjang - Deanna Durbin Hutagalung; Dian Megasari; Saprudin (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The use of cellular telephones or commonly abbreviated as cell phones is increasingly widespread in society, there are many positive impacts and benefits obtained in the fields of education, health, security and business. In the field of education, the use of mobile phones is really needed, especially during the Covid 19 era, namely as a medium for online learning and sharing information. Currently, cellphones have begun to change their function, not only as communication and information tools but also for playing games, listening to music, watching films and so on. Cell phones also have various price and feature options which are equipped with various increasingly sophisticated and intelligent technologies so that they are often called smartphones. Various information and applications can be accessed along with the increasing number of websites that can be accessed via smartphone which provide information in the form of news, job vacancies, and so on. Apart from having a positive impact, using a smartphone also has a negative impact if it is not used properly. For teenagers, it can cause them to lose concentration in studying because they only focus on various information and social media and games. Apart from that, it can damage the eyes, damage the spine due to lack of movement and sitting more, hearing problems due to using headsets, sleep disturbances due to staying up too late and decreased sense of family and social factors. Inseparable part of our daily lives, playing a central role in connecting us with the virtual world. However, with all the comfort and benefits offered, we often tend to forget the security aspects that are no less important. Seeing the importance of security factors, security awareness of smartphone use is something that cannot be ignored. Smartphone users personally suffer a lot from fraud through WhatsApp or SMS applications, game applications which without realizing it are a place for gambling and also illegal online loan offers which cause a lot of harm to the public. Smartphone users, especially children and teenagers, often don't realize things like this. Therefore, users must be responsible for their personal security in the digital world, such as installing antivirus, not sharing confidential personal data, choosing when to access information on the internet, and so on. Therefore, it is necessary to spread awareness about the safety of using smartphones, especially among teenagers.